Penggunaan Media Sosial dengan Pendekatan Model AIDA bagi Usaha Kecil dan Menengah - Syastra, Muhammad Taufik; Adam, Steffi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
Small Medium Enterprise (SMEs) have a strategic role in the development of a country. Every SME needs to improve its competitive advantage. One way to improve the competitive advantage is to utilize social media in running the business. The research aims to This study aims to implement the use of social media with reference to the AIDA Model for SMEs. Â The fresearch focuses on social media facebook. SMEs are given training in using social media. Training participants as respondents from this research are 20 SMEs. The data analysis technique used is Miles and Hubermann. Results from this study indicate that the AIDA model can be used as an approach in using social media facebook. A total of 20 SMEs have been trained to use social media facebook based on AIDA model